Lèche-vitrines: Human Identity and the Mannequin in Au Bonheur des Dames. (3rd April 2022) - Foster, Kate
ABSTRACT: The department store mannequin is often read as representative of commodity or sexual fetishism and, consequently, of woman objectified. This article posits that in Émile Zola's Au Bonheur des Dames (1883), the mannequin can highlight such objectification to the woman in the text. Through close readings of the text's mannequins this article seeks to analyse the combination of estrangement and excitement which characterizes the experience of living under modernity. It asks whether the headless Zolian mannequin empowers the shopper to recognize and thus reject objectification of the self, or if it is simply a disquieting reminder of one's own powerlessness.